Improving radiologic communication in oncology: a single-centre experience with structured reporting for cancer patients - Weber, Tim; Spurny, Manuela; Hasse, Felix; Sedlaczek, Oliver; Haag, Georg Martin; Springfeld, Christoph; Mokry, Theresa; Jäger, Dirk; Kauczor, Hans-Ulrich; Berger, Anne Katrin (Insights into imaging, 2020)
Our aim was to develop a structured reporting concept (structured oncology report, SOR) for general follow-up assessment of cancer patients in clinical routine. Furthermore, we analysed the report quality of SOR compared to conventional reports (CR) as assessed by referring oncologists.